ATOPIC DERMATITIS - L.S. Namazova; Yu.G. Levina; A.G. Surkov; K.E. Efendieva; I.I. Balabolkin; T.E. Borovik; N.I. Voznesenskaya; L.F. Kaznacheeva; L.P. Mazitova; G.V. Yatsyk (Union of pediatricians of Russia, 2006)
.